PERANCANGAN PEMESANAN AIR BERSIH ATAU AIR GUNUNG BERBASIS WEBSITE - Irene Adriana Putri Andini; Ahmad Nugroho (UNIVERSITAS STEKOM, 2024)
In the midst of technology users in Indonesia, there are still many business fields that have not maximized technological advances for their business, one of which is the Berkah Dalem clean water depot business located in Mijen, Kebonagung, Central Java. In the problems that exist in this study, it is known that the order acceptance system at the Berkah Dalem clean water depot still uses a manual method which is less effective and efficient. Therefore, the purpose of this study is to design a website-based clean water ordering system and create sales and order information data that can be accessed easily. The method used is the waterfall method for software development using XAMPP. The results achieved are the design of a website-based ordering system has passed the feasibility test of using the system with data that all status tests are accepted, so it can be concluded that the designed system is successful and can be applied to the clean water depot business.